Tráfico internacional de pessoa para fim de exploração sexual :uma análise a partir da implementação da política nacional de enfrentamento ao tráfico de pessoas e sua aplicação no Estado do Rio Grande do Sul - Martins, Felipe Antunez (2015)
This research falls in the area of concentration Criminal System and Violence, in the line of research called violence, crime and public security linked to Post graduate Program of Criminal Sciences. It analysis the international sexual traffic for exploitation purposes in the state of Rio Grande do Sul. This in the first chapter it aimed to analysis the main aspects of the commercial sex industry in particular prostitution, sex tourism and pornography. In the same chapter the international crime of trafficking in person for purposes of sexual exploitation has been analyzed as well as the main international routes recorded from entry and exit points of the country. In the second chapter, there was an analysis of Brazilian legislation concerning the criminal offense of international trafficking in person for purposes of sexual exploitation, and also the concept and analysis along the lines of the Additional Protocol to Prevent, Suppress and Punish Trafficking in Persons especially Women and Children.Also in this chapter, we analyzed the case registered by the Federal Regional Courts. The third chapter is entered on the analysis of the National Policy and National Plan of Combat Trafficking in Persons created in the country, from the year 2006. Finally, in the fourth chapter, is entered on the interviews with the members of the institutions relation to the various axes of confronting human trafficking, and thus were unable to verify how the National Policy to Combat Human Trafficking was implemented in the state of Rio Grande do Sul, and also the institutions involved in this crime are fighting it. The period for analysis is from January 2006 to December 2013.